South Africa Financial Ombud System Diagnostic - World Bank (World Bank, Washington, DC, 2021)
The Finance, Competitiveness and Innovation Global Practice of the World Bank Group (WBG) aims to help countries build financial systems that are deep, diversified, inclusive, efficient, and stable essential to promoting economic growth, reducing poverty, and increasing shared prosperity. One core activity is supporting national authorities to achieve their objectives for financial inclusion, by supporting policy, legal, regulatory, and supervisory reforms in areas such as financial consumer protection, including financial-sector alternative dispute resolution (ADR). Through the South Africa Financial Sector Development and Reform Program, the WBG is supporting the national reform process, which includes achieving an efficient and effective ADR system, so that financial customers can hold financial institutions to account if there is a dispute. This diagnostic review valuates the current financial-sector Ombud system in South Africa, Compares it against international good practice, and recommends reforms to provide good-quality outcomes and good value for money for the future.